Optimizing Organizational Commitment Through Organizational Culture - Tantri Hutagaol, Apri; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
One of the companies that carries out human resource management is BPJS Ketenagakerjaan (Employment Social Security Administering Agency) which is a public program that provides protection for workers to overcome certain socio-economic risks and its implementation uses social insurance mechanisms as a State institution that operates in the insurance sector. social BPJS Ketenagakerjaan, formerly known as PT Jamsostek (Persero), is the implementer of the labor social security law. The results of this research are as follows: Organizational Culture has a positive and significant effect on Organizational Commitment with a value of 0.431 and a sig of 0.000. Teamwork has a positive and significant effect on Organizational Culture with a value of 0.347 and sig 0.001. Teamwork has a positive and significant effect on Organizational Commitment with a value of 0.380 and sig 0.001. Organizational Citizenship Behavior has a positive and significant effect on Organizational Culture with a value of 0.573 and a sig of 0.000. Organizational Citizenship Behavior has a positive and significant effect on Organizational Commitment with a value of 0.113 and a sig of 0.204. Teamwork has a positive and significant indirect effect on Organizational Commitment through Organizational Culture with a value of 0.150 and a sig of 0.007. Organizational Citizenship Behavior has a positive and significant indirect effect on Organizational Commitment through Organizational Culture with a value of 0.247 and a sig of 0.000.